Optimization methods for financial index tracking from theory to Ppactice - Benidis, Konstantinos; Feng, Yiyong; Palomar, Daniel P. (Foundations and trends in optimization, 2018)
An in-depth overview of the index tracking problem analyzing all the caveats and practical issues an investor might have, such as the frequent rebalancing of weights, the changes in the index composition, the transaction costs, etc